REVIEW OF INDONESIAN LEGAL ARRANGEMENT ON TUNA FISHERIES - Ariadno, Melda Kamil (Indonesian Journal of International Law, 2013)
High seas fishery is very strategic to Indonesia mostly because of tuna fisheries in which Indonesia plays a quite substantive role as the major tuna exporting country in the world. International law provides comprehensive high seas management system through the adoption of various treaties and the establishment of regional fisheries management organizations (RFMOs). Challenge to Indonesian Government thus whether Indonesia could apply genuinely the high seas fishing management measures and comply with RFMOs of which Indonesia is member. Substantial rules and regulations have been adopted by Indonesia and yet the major question remains whether Indonesia is ready to exercise its obligations under high seas fisheries regime.